Alcohol consumption in patients with cardiovascular diseases (results of the survey of cardiac patients in outpatient practice) - O. D. Ostroumova; I. E. Nikolaeva; S. Ya. Eregin; I. V. Pokrovskaya; K. A. Ishchenko (Столичная издательская компания, 2015)
Aim. To study the frequency and characteristics of alcohol use in outpatients with cardiovascular diseases and to determine their preferences regarding the help in limiting alcohol consumption.Material and methods. Voluntary and anonymous survey using AUDIT-C and CAGE questionnaires was conducted in 199 patients. The data of 182 patients (82 women and 100 men, mean age 56.4±5.8 years) was included in the analysis.Results. Arterial hypertension (70%), heart rhythm disorders (25%), ischemic heart disease (20%), functional class I-II chronic heart failure (21%) predominated among all clinical entities. Positive AUDIT-C test was found in 30% of men and 7.3% of women. 17% of men and 23.2% of women did not use alcohol at all. Positive responses to all 4 questions of the CAGE test were given by 3% of men and none of women, positive answers to 3 questions - by 15% of men and none of women, to 2 questions - by 17% of men and 11% of women. Positive answer to the question about the need to reduce alcohol consumption was given by 36% of men and 13.4% of women.Conclusion. Simultaneous testing using AUDIT-C and CAGE questionnaires in outpatients with cardiovascular diseases allows identifying a subgroup of patients (more in men) who have a potential problem with an excessive alcohol consumption and need to reduce the intake of alcoholic beverages.